Numerical schemes for a class of tempered fractional integro-differential equations - Sultana F.; Singh D.; Pandey R.K.; Zeidan D. (My University, 2025)
For a class of tempered fractional integro-differential equation of the Caputo type, a comparative study of three numerical schemes is presented in this paper. The schemes discussed are Linear, Quadratic and Quadratic-Linear schemes. Four numerical examples are considered to discuss error estimate and convergence order of the numerical schemes for different values of step-size h and the parameter λ. Numerical results are presented through tables and figures which validate the analytical solution of the test examples. Further, the comparative performances of the presented numerical schemes are discussed. © 2020 IMACS